2007
DOI: 10.2105/ajph.2005.071522
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Influences on Modern Contraceptive Use in Sub-Saharan Africa

Abstract: Aspects of a community's sociocultural and economic environment appear to influence a woman's use of modern contraceptive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
222
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(251 citation statements)
references
References 15 publications
29
222
0
Order By: Relevance
“…First, we grouped women (and men) from a PSU to represent the aggregate belief in myths for individuals in that PSU, which is the standard approach for analyses of community-level influences using DHS data. 2729,37 However, the use of PSUs to represent urban communities may not have been the best strategy, because women in urban settings may be influenced by individuals outside of their community (e.g., where they work, shop and visit). Future analyses that examine the cohesion of urban communities will help determine how to define “community” in complex urban settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we grouped women (and men) from a PSU to represent the aggregate belief in myths for individuals in that PSU, which is the standard approach for analyses of community-level influences using DHS data. 2729,37 However, the use of PSUs to represent urban communities may not have been the best strategy, because women in urban settings may be influenced by individuals outside of their community (e.g., where they work, shop and visit). Future analyses that examine the cohesion of urban communities will help determine how to define “community” in complex urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focused on community-level health outcomes have examined whether socioeconomic status, supply environment and quality of health care are associated with a health behavior or outcome–that is, these studies have demonstrated that women's (or men's) behaviors are associated with the behaviors or attitudes of other who live around them. 2733 For example, Speizer et al found that the increasing prevalence of sexual violence reported by women within a community was negatively associated with women's use of condoms at last sex and positively associated with their being HIV positive or having had an adolescent pregnancy; 34 other studies among adults found similar results. 27,35,36 And according to an analysis of 2005–2009 DHS data from 21 African countries, contraceptive use remained associated with community demographics and fertility norms, community-level gender norms and inequalities, and health knowledge after individual factors were controlled for.…”
mentioning
confidence: 98%
“…Use of modern contraceptives was positively associated with women's BMI and household use of adequately iodized salt. Previous research has shown that modern contraceptive users tend to have higher education levels and exposure to information in media and to come from wealthier households (40) . Because our analysis has adjusted for education and wealth index, the noted 'modern contraceptive use' effect on BMI and use of adequately iodized salt goes beyond these two factors and may be an indicator A general lack of awareness of existing programmes or products such as iodized salt may lead to lower levels of demand and use, and cultural preference for locally produced non-iodized salt may also hinder consumption of the imported iodized salt (41) .…”
Section: Discussionmentioning
confidence: 99%
“…However, research in South Africa to date has not identified factors associated with women's increased risk of having an AEP. In South Africa, social norms favouring fertility and childbearing (Wood & Jewkes, 2006); barriers to attendance of and access to family planning clinics (Stephenson, Baschieri, Clements, Hennink, & Madise, 2007); and a lack of accurate and complete information about how to use contraceptives effectively (Beksinska, Rees, Nkonyane, & McIntyre, 1998) are among factors that prevent contraceptive use.…”
mentioning
confidence: 99%